2004
DOI: 10.1016/j.physa.2004.03.096
|View full text |Cite
|
Sign up to set email alerts
|

Decay rate and decoherence control in coupled dissipative cavities

Abstract: We give a detailed account of the derivation of a master equation for two coupled cavities in the presence of dissipation. The analytical solution is presented and physical limits of interest are discussed. Firstly we show that the decay rate of initial coherent states can be significantly modified if the two cavities have different decay rates and are weakly coupled through a wire. Moreover, we show that also decoherence rates can be substantially altered by manipulation of physical parameters. Conditions for… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…We can see that the master equation contains extra terms due to the transformation to normal modes. The full treatment for arbitrary κ a and κ b makes analytical progress quite difficult 28 and a numerical calculation may be presented elsewhere. However, the simple regime in which both resonators decay with similar rates can be readily investigated.…”
Section: Yurke-stoler State and Inclusion Of Dissipation In The mentioning
confidence: 99%
“…We can see that the master equation contains extra terms due to the transformation to normal modes. The full treatment for arbitrary κ a and κ b makes analytical progress quite difficult 28 and a numerical calculation may be presented elsewhere. However, the simple regime in which both resonators decay with similar rates can be readily investigated.…”
Section: Yurke-stoler State and Inclusion Of Dissipation In The mentioning
confidence: 99%
“…In Ref. [21] it is shown that, for identical cavities and zero temperature, the model leads to the master…”
Section: A Finite Interaction Times and Lossy Cavitiesmentioning
confidence: 99%
“…The result of such interaction in the low energy domain is a collective excitation which for all practical purposes behaves as a bosonic degree of freedom. The language of Thouless theorem is very sophisticated and hard to understand for nonspecialists; however, it may turn out to be quite useful in systems which involve only few degrees of freedom, as we often encounter in quantum optics [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In these situations, it is usually convenient to rewrite the creation and annihilation bosonic operators in a new form, and it becomes necessary to find out the new eingenstates.…”
Section: Introductionmentioning
confidence: 99%